Kritik terhadap Wacana Patriarki dalam Novel La Civilisation, ma Mère !... Karya Driss Chraïbi - Fina Falahu Sani (Universitas Mulawarman, 2023)
Moroccan francophone literature raises various criticisms, especially the issues of colonialism and gender. Driss Chraïbi is a Moroccan writer who investigated these issues in La Civilisation, ma Mère !.... This novel is told from the male perspective of a mother’s struggle in fighting gender discrimination in the French Protectorate, which later gives rise to a critique. This article aims to analyse how the critique of the patriarchal discourse is constructed in the novel. The method being used is qualitative and is supported by Roland Barthes’s narrative structure theory, A.J. Greimas’ actantial scheme theory, Gérard Genette’ focalization theory, and theory of postcolonial feminism by Gayatri Spivak. The result of this article is the critique on the patriarchal discourse is constructed through the postcolonial discourse that utilises the disposition of the “I” character as the indigenous man of the young generation, who encourages the deployment of Western culture to civilize women. Modern civilisation also becomes a hero for the Mother character, which is a subaltern, in her success in realising freedom and diminishing patriarchal discrimination. Nevertheless, her mindset and mental condition are still colonized due to her adjacency to the colonial legacy of the West.